Developing Multi-Frequency Bioelectrical Impedance Analysis for Fat-Free Mass Estimation in Early Childhood - Wismaya, Herenda Sela; Sugianto, Wahyu; Hanifah, Rida Dwi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
This study aims to develop and evaluate a Multi-Frequency Bioelectrical Impedance Analysis (MFBIA) system for estimating body composition, specifically Fat-Free Mass (FFM) and Body Fat Percentage (BF%). The primary objective was to assess the accuracy and reliability of the MFBIA system by comparing its measurements with those obtained from a commercially validated Smart Body Fat analyzer and traditional anthropometric methods. The research involved regression analysis to examine the correlation between FFM and BF% measurements from MFBIA and anthropometric data, including height and weight. Additionally, impedance measurements were taken at multiple frequencies (25 kHz, 50 kHz, and 100 kHz) to determine the system's ability to estimate body composition parameters across various conditions. The results showed a strong correlation between the FFM and BF% values ​​derived from MFBIA and those obtained using the Smart Body Fat analyzer. The regression analysis indicated high linearity, with R² values ​​ranging from 0.9439 to 0.9692, signifying the robustness of the system in predicting body composition. Furthermore, the MFBIA system demonstrated a high degree of consistency and accuracy in measuring FFM and BF%, with minimal deviations from the reference device. This research presents a multi-frequency BIA device designed specifically to measure fat-free mass (FFM), an important indicator for assessing the nutritional status of children. The results of this research offer a practical, affordable, and non-invasive tool for healthcare providers to assess body composition in children. The MFBIA system has the ability to track nutritional status, supporting targeted interventions to promote child health and prevent stunting.